2002
DOI: 10.1038/sj.ejcn.1601338
|View full text |Cite
|
Sign up to set email alerts
|

Resistant starch content in a selection of starchy foods on the Swedish market

Abstract: Objective: The objective was to determine the resistant starch (RS) content in a selection of typical starchy foods on the Swedish market. In addition, the daily RS intake was estimated from Swedish food consumption data. Design: The major forms of RS, including physically encapsulated starch, were determined with an in vitro method using chewing as a pre-step before enzymatic incubation. Setting: The study was performed at the Department of Applied Nutrition and Food Chemistry, Lund University, Sweden. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The great differences in the ratios of soluble starch (SS) over RS (235 for wheat (W), 112 for rye (R), and only 22 for barley (B)) verify previous observations that the starch in whole grains is apparently more resistant to digestion than refined starch (Stephen, 1994). The great value of the ratio SS/ RS (¼ 204) observed for oat flakes is comparable to that of wheat and could be explained with previous observations of Liljeberg Elmståhl (2002) who found that extruded and puffed breakfast cereals have a low RS content. Thus, the low RS values observed for oat flakes meal could be related to the treatment before the flaking procedure, during which oat grains are steamed at high temperature to inhibit the lipase enzyme, promoting a high degree of starch gelatinization.…”
Section: Composition Of Flourssupporting
confidence: 87%
“…The great differences in the ratios of soluble starch (SS) over RS (235 for wheat (W), 112 for rye (R), and only 22 for barley (B)) verify previous observations that the starch in whole grains is apparently more resistant to digestion than refined starch (Stephen, 1994). The great value of the ratio SS/ RS (¼ 204) observed for oat flakes is comparable to that of wheat and could be explained with previous observations of Liljeberg Elmståhl (2002) who found that extruded and puffed breakfast cereals have a low RS content. Thus, the low RS values observed for oat flakes meal could be related to the treatment before the flaking procedure, during which oat grains are steamed at high temperature to inhibit the lipase enzyme, promoting a high degree of starch gelatinization.…”
Section: Composition Of Flourssupporting
confidence: 87%
“…Whole-grain bread, with a more intact structure, was shown to improve postprandial glycaemic and insulinaemic responses compared with whole-wheat bread made from milled flour ( 86 ) . In bread made from 80 % barley kernels and 20 % white wheat flour, as much as 26 % RS (total starch basis) was found ( 87 ) . The addition of buckwheat ( Fagopyrum esculentum ) whole seeds to white wheat flour in bread products (30–70 %) increased the RS level (2·3–3·2 %) since all three types of RS were likely to be present ( 87 ) .…”
Section: Strategies For Reducing the Glycaemic Index Of Breadmentioning
confidence: 99%
“…Bednar et al . 2001; Liljeberg Elmstahl 2002; see Table 8, which illustrates the substantial contribution that resistant starch can make to the total amount of non‐digestible material present).…”
Section: Food Sources Of Carbohydrates and Dietary Fibrementioning
confidence: 99%
“…2001) – quantification of resistant starch portion involved setting up an in vitro model of digestion using bacteria isolated from faeces. Liljeberg Elmstahl (2002) – quantification of resistant starch involved chewing and then enzymic incubation according to the method of Akerberg et al . (1998).…”
Section: Food Sources Of Carbohydrates and Dietary Fibrementioning
confidence: 99%